Gibberellic acid maintains postharvest quality of Agaricus bisporus mushroom by enhancing antioxidative system and hydrogen sulfide synthesis. Issue 10 (20th September 2021) - Zhu, Dan; Wang, Chaoping; Liu, Ye; Ding, Yang; Winters, Emily; Li, Wenxiang; Cheng, Fansheng
Abstract: The application of gibberellic acid (GA3 ) treatment to the postharvest quality maintenance of white button mushroom ( Agaricus bisporus ) was investigated. The optimum concentration of exogenous GA3 was 100 mg/L. At this concentration, the color change was inhibited, the firmness was maintained, and the weight loss and respiratory rates were reduced. The GA3 group had significantly lower malonaldehyde (MDA) content and membrane permeability. Reactive oxygen species accumulation was reduced due to the regulation of polyphenol oxidase (PPO), peroxidase (POD), and superoxide dismutase (SOD) enzyme activities. Moreover, the production of endogenous gaseous signaling molecule hydrogen sulfide (H2 S) was triggered by GA3 treatment, which enhanced cystathionine γ‐lyase (AbCSE) and cystathionine β‐synthase (AbCBS) activities alongside the corresponding gene expressions. The preservation of button mushroom postharvest storage quality by GA3 was most likely due to the regulation of reactive oxygen species metabolism and hydrogen sulfide biosynthesis. Practical applications: Mushroom is rich in nutrients and functional substances. However, due to the lack of cuticle, high respiration rate, and moisture content, mushroom's postharvest quality deteriorates rapidly. A safe and effective reagent that prevents the senescence and quality deterioration of harvested mushroom is urgently needed. The effects of plant hormone GA3 on the postharvest quality of edible fungi remain unclear. The present study provided convincing evidence that 100 mg L −1 of GA3 effectively maintained postharvest button mushroom quality by regulating reactive oxygen species metabolism and hydrogen sulfide biosynthesis. Abstract : Exogenous GA3 is effective in inhibiting the postharvest senescence of button mushroom. The cleavage of ROS is triggered by the GA3 treatment by regulating the antioxidative system. Moreover, GA3 stimulates the endogenous H2 S biosynthesis, which antagonizes the effect of ethylene.